Preparation method of a high-quality columnar crystal AlNiCo magnetic material
By spraying a high-temperature and heat-resistant inorganic coating on the surface of the crystallizer panel, the risk of directional crystallizer caused by the impact of high-temperature molten steel is solved, and the preparation of high-quality columnar crystals and material utilization is improved.
Patent Information
- Application Number
- CN202310813018.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-04
- Publication Date
- 2025-08-01
- Estimated Expiration
- 2043-07-04
AI Technical Summary
The prior art is difficult to effectively resist the impact of high-temperature molten steel during the preparation process of aluminum nickel cobalt magnetic steel, forming a reasonable temperature gradient, resulting in the risk of "biting plates" or casting in a directional crystallizer, affecting the utilization rate and safety of materials.
A layer of inorganic coating is sprayed on the surface of the crystallizer panel, and a dense, high temperature resistant and thermal conductivity is formed using plasma spraying technology to form a dense, high temperature resistant and thermal conductivity coating, adjust the directional crystallization rate, prevent the crystallization panel from being poured by steel, and maintain a good cooling effect.
The preparation of thick and high-quality columnar crystal aluminum nickel magnetic materials has been achieved, which improves the material utilization rate and the service life of the crystallizer panel, and reduces production risks.
Smart Images

Figure BDA0004320629250000071
Abstract
Description
Technical Field
[0001] The present invention relates to the field of permanent magnet materials, and particularly to a method for preparing a high-quality columnar crystal alnico magnetic material. Background Art
[0002] According to the presence or absence of columnar crystals in the crystal structure, cast alnico magnets are divided into directional and non-directional. Among them, directionally cast alnico magnets have been widely used due to their good coercivity and excellent magnetic energy product. In the manufacture of directionally cast alnico magnets, most enterprises currently use the high-temperature casting method for production, that is, placing a high-temperature heated mold on the water-cooled crystallizer panel, and then using a top-pouring casting system to directly pour the high-temperature molten steel into the mold from the riser. Through the heat exchange of the water-cooled crystallizer panel, during the solidification process of the ingot, the liquid-solid interface steadily advances along the solidification direction in a planar manner, and then thick and straight columnar crystals are obtained. To meet this condition, the temperature gradient in front of the solid-liquid interface needs to be as large as possible, and the cooling rate of the crystallizer panel needs to be as small as possible. Therefore, in the process, the method of increasing the pouring temperature of the molten steel and reducing the cooling water pressure or water temperature is often adopted. However, in the actual production process, there are upper limits to the increase of the molten steel temperature and the decrease of the cooling rate. And too high a molten steel temperature is likely to cause splashing of the alloy liquid and violent volatilization of alloy elements (Al, Ti) during the melting process, causing a strong reaction between the alloy liquid and the crucible material, and then affecting the performance. Moreover, during the casting process, the molten steel is poured into the sand mold through the riser, and the high-temperature molten steel impacts the crystallizer. At this time, when the cooling rate is too small or insufficient, there is a high risk of "biting the plate" or even pouring through the directional crystallizer, which may then cause a greater production safety accident.
[0003] In some literature reports, some technical processes adopt the method of opening the cooling water during casting and closing the cooling water after casting to reduce the risk of crystallizer penetration and improve the cooling rate. This method is simple and effective, but in the continuous production process, manual control cannot ensure consistency, and machine control puts higher equipment requirements on the entire casting system. Moreover, excessive cooling during casting will form "constitutional supercooling" at the solid-liquid interface, resulting in equiaxed crystals (non-directional, unusable, and need to be removed in subsequent processing) at the bottom of the ingot, thereby affecting the material utilization rate.
[0004] Therefore, it is extremely important to find a simple and efficient method that can effectively resist the impact of high-temperature molten steel, reasonably conduct heat radiation, and form a good temperature gradient at the solid-liquid interface to prepare a directional alnico magnet with straight and thick columnar crystals. Summary of the Invention
[0005] To solve the above technical problems, the present invention provides a method for preparing a high-quality columnar crystal aluminum-nickel-cobalt magnetic material. The present invention uses plasma spraying technology to spray an inorganic coating on the surface of the crystallizer panel. First, the coating has a high density and better adhesion to the substrate; second, the coating can withstand high-temperature molten steel at least at 1750 °C, avoiding the crystallizer panel being penetrated by molten steel; third, the coating also has excellent thermal conductivity and does not affect the directional cooling effect of the crystallizer panel, so that finally high-quality columnar crystals that are thick and tall can be obtained.
[0006] The specific technical solution of the present invention is: a method for preparing a high-quality columnar crystal aluminum-nickel-cobalt magnetic material, comprising the following steps:
[0007] 1) Plasma spray the coating material on the surface of the crystallizer panel to form a uniform coating; the coating material is one or more of Si3N4, AlN or BN, and the particle size is 30μm ≤ D50 ≤ 50μm.
[0008] 2) Melt the raw materials of aluminum-nickel-cobalt, stir evenly, and pour them into a sand mold placed on the crystallizer panel. A cooling water column is passed through the bottom of the crystallizer panel. After crystallization, remove the sand mold, let it stand and cool, remove the sand mold to obtain a blank, and remove the fine crystal part at the bottom and the non-columnar crystal part at the top of the blank to obtain a rough columnar crystal blank;
[0009] 3) Process the rough columnar crystal blank into a finished shape.
[0010] 4) Perform solution heat treatment, cooling, heat preservation magnetization, and tempering treatment on the blank of the finished shape obtained in step 3) to obtain a semi-finished blank.
[0011] 5) Perform finish machining on the semi-finished blank to obtain a finished product.
[0012] The present invention effectively adjusts the rate of directional crystallization and improves the durability of the mold panel by spraying the mold panel, thereby obtaining high-quality columnar crystal Alnico. Specifically, the present invention uses plasma spraying technology to spray an inorganic coating on the surface of the mold panel. First, compared with traditional spraying technologies, the coating formed by plasma spraying technology has a high density and better adhesion to the substrate. Second, the coating formed with Si3N4, AlN or BN as raw materials has excellent high-temperature resistance and can withstand molten steel at a high temperature of at least 1750 °C, so the crystallization panel can be prevented from being penetrated by molten steel. Third, compared with conventional high-temperature resistant coating materials such as kaolin and quartz sand, the coating material of the present invention not only has high-temperature resistance but also excellent thermal conductivity, so it will not affect the directional cooling effect of the mold panel, and finally high-quality columnar crystals that are thick and relatively tall can be obtained (although the temperature resistance of coating materials such as kaolin and quartz sand is excellent, their thermal conductivity is poor, which will greatly reduce the directional cooling rate. Therefore, even if relatively thick columnar crystals can be obtained, their height is greatly limited).
[0013] Preferably, in step 1), the thickness of the mold panel is 15-25 mm, and the thickness of the coating is 1-4 mm.
[0014] The coating thickness will affect the cooling and crystallization effect. If the coating thickness is too thick, the overall heat transfer rate of the mold panel will be reduced, which will in turn affect the thickness and height of the columnar crystals. If the coating is too thin, it is not conducive to the mold panel to resist the impact and melting of the molten steel during casting, and the risk of penetration is very likely to occur.
[0015] Preferably, in step 1), during plasma spraying, first use a coating material with a particle size D50 = 40-50 μm, and the coating thickness does not exceed 20% of the total coating thickness; then use a coating material with a particle size D50 = 35-40 μm, and at this time the coating thickness does not exceed 50% of the total coating thickness; finally use a coating material with a particle size D50 = 30-35 μm to obtain a mold panel with a uniform coating attached to its surface.
[0016] The present invention uses a step-by-step spraying method to strengthen the adhesion between the coating and the mold panel, improve the pores between the coatings, and enhance the stability of the coating to resist high-temperature impact. Compared with one-step spraying, this method of step-by-step spraying using spraying sources with different particle sizes has a decreasing particle size. The small particle size is used to cover the voids of the previous layer of coating, and they are stacked layer by layer. An interlaced flat layer structure can be formed between the coatings. The coating is denser, more uniform, has a stronger ability to resist thermal shock, and a longer service life. In addition, considering materials with different particle sizes, their adhesion force is generally inversely proportional to the particle size. Therefore, it is necessary to optimize and control the thickness of each layer to make the stacked layers closer.
[0017] Preferably, in step 1), the material of the mold panel is low-carbon steel.
[0018] Preferably, in step 1), before plasma spraying, the surface of the mold panel is polished to be smooth and flat and cleaned.
[0019] Preferably, in step 1), the plasma gas for the plasma spraying is nitrogen.
[0020] Preferably, in step 2), the alnico comprises raw materials in the following mass percentages: 7-8% of Al, 30-35% of Co, 2-3% of Cu, 12-14% of Ni, 0.6-0.8% of Ti, 0.05-0.15% of FeS, 0.05-0.08% of C, and the balance being Fe.
[0021] Preferably, in step 2), the melting sequence is as follows: Co, Ni, Cu and Fe are melted first. After the molten steel temperature rises above 1500 °C, FeS and C are added, and then Ti and Al are quickly added until the temperature reaches 1650-1750 °C, heating is stopped, stirred evenly, and casting is carried out immediately after melting.
[0022] Preferably, in step 2), the mold panel is heat-treated before use and then cooled to room temperature; the heat treatment temperature is 950±20 °C, the vacuum degree is lower than 5×10 -2 Pa, and the time is 2-4 h.
[0023] Through the above heat treatment, the internal structure of the sprayed mold panel can be made more dense and uniform, and its hardness, service life, etc. can be improved. In addition, the bonding force between the coating and the original structure of the steel plate can be increased, and its adhesion can be promoted.
[0024] Preferably, in step 2), the melting temperature is 1650-1750 °C.
[0025] Preferably, in step 2), the pressure of the cooling water column is 0.8-1.2 Kg, the water temperature is 25-°30 C, and the water column height is 25-35 mm (the distance from the nozzle to the mold panel).
[0026] Adopting the above cooling method can prevent the mold panel from being penetrated by high-temperature molten steel to the greatest extent, and the cooling rate is not too fast / slow, so as to obtain better columnar crystals.
[0027] Preferably, in step 2), the crystallization time is 30-40 min, and the sand mold is removed after standing and cooling to room temperature.
[0028] Preferably, in step 4), the solution heat treatment temperature is 1260-1300 °C, and the time is 20-40 min.
[0029] Preferably, in step 4), it is cooled to 800 - 900 °C.
[0030] Preferably, in step 4), the magnetization time is 20 - 30 min.
[0031] Preferably, in step 4), the tempering treatment includes: first insulating at 610 - 625 °C for 3 - 4 h, then insulating at 580 - 595 °C for 4 - 6 h, then insulating at 550 - 565 °C for 4 - 6 h, and finally air - cooling to room temperature.
[0032] Preferably, in step 5), the finish machining is to finely grind the semi - finished blank, remove defects such as scale on the surface, clean it, and obtain the finished product.
[0033] Compared with the prior art, the beneficial effects of the present invention are as follows: The present invention uses plasma spraying technology to spray an inorganic coating on the surface of the mold panel. First, the coating has high density and better adhesion to the substrate; second, the coating can withstand high - temperature molten steel at least at 1750 °C, which can prevent the mold panel from being penetrated by molten steel; third, the coating also has excellent thermal conductivity and does not affect the directional cooling effect of the mold panel, so that finally thick and high - quality columnar crystals can be obtained. Specific Embodiments
[0034] The following further describes the present invention with reference to embodiments.
[0035] General Embodiment
[0036] A method for preparing a high - quality columnar crystal Alnico magnetic material includes the following steps:
[0037] 1) Grind the surface of the mold panel (low - carbon steel (preferably 45# steel plate), 15 - 25 mm thick) to be smooth and clean, and plasma - spray (preferably nitrogen) the coating material (one or more of Si3N4, AlN or BN, with particle size 30 μm ≤ D50 ≤ 50 μm) on the surface of the mold panel to form a uniform coating (1 - 4 mm thick). Specifically: First, use a coating material with D50 = 40 - 50 μm, and the coating thickness does not exceed 20% of the total coating thickness; then use a coating material with D50 = 35 - 40 μm, and at this time the coating thickness does not exceed 50% of the total coating thickness; finally, use a coating material with D50 = 30 - 35 μm to obtain a mold panel with a uniform coating attached to its surface.
[0038] 2) First perform heat treatment on the mold panel, and then cool it to room temperature; the heat treatment temperature is 950 ± 20 °C, and the vacuum degree is lower than 5*10 -2Pa for 2 - 4 h. Melt the raw materials of alnico (Al 7 - 8%, Co 30 - 35%, Cu 2 - 3%, Ni 12 - 14%, Ti 0.6 - 0.8%, FeS 0.05 - 0.15%, C 0.05 - 0.08%, the rest is Fe) at 1650 - 1750 °C in the following order: first melt Co, Ni, Cu and Fe. When the molten steel temperature rises above 1500 °C, add FeS and C, then quickly add Ti and Al until the temperature reaches 1650 - 1750 °C, stop heating, stir evenly, and immediately pour the molten metal into the sand mold placed on the crystallizer panel after melting. There is a water column at the bottom of the crystallizer panel (pressure is 0.8 - 1.2 Kg, water temperature is 25 - 30 °C, water column height is 25 - 35 mm (distance from the nozzle to the crystallizer panel)). After crystallization for 30 - 40 min, remove the sand mold, let it stand and cool to room temperature, then remove the sand mold to obtain a blank. Remove the fine crystal part at the bottom and the non-columnar crystal part at the top of the blank to obtain a rough columnar crystal blank.
[0039] 3) Process the rough columnar crystal blank into the finished shape.
[0040] 4) Solution heat treat the blank with the finished shape obtained in step 3) at 1260 - 1300 °C for 20 - 40 min, cool to 800 - 900 °C, place it in a magnetic field for heat preservation and magnetization for 20 - 30 min, and then perform tempering treatment. Specifically, first keep it at 610 - 625 °C for 3 - 4 h, then at 580 - 595 °C for 4 - 6 h, then at 550 - 565 °C for 4 - 6 h, and finally air cool to room temperature to obtain a semi-finished blank.
[0041] 5) Finish grinding the semi-finished blank, remove defects such as oxide scale on the surface, and clean it to obtain the finished product.
[0042] Example 1
[0043] 1) Take a 20 - mm - thick crystallizer panel (45# steel plate), polish the surface smooth and flat, wipe it clean with alcohol, and spray a 1 - mm BN coating on the panel surface using the nitrogen plasma spraying process: first use coating material with D50 = 45 μm, and the coating thickness is 0.2 mm; then use coating material with D50 = 35 μm for spraying, and at this time the coating thickness is 0.5 mm; finally use coating material with D50 = 30 μm to obtain a crystallizer panel with a uniform coating attached to the surface.
[0044] 2) First perform heat treatment on the crystallizer panel, and then cool it to room temperature; the heat treatment temperature is 950 °C, and the vacuum degree is lower than 5 * 10 - 2Pa, with a time of 2 h. Weigh the corresponding mass fractions of metallic elements, where: Al: 7.5%; Co: 35%; Cu: 2%; Ni: 13%; Ti: 0.6%; FeS: 0.1%; C: 0.05%, and the rest is Fe. The melting charging sequence is as follows: Co, Ni, Cu and Fe are first melted. After the molten steel temperature rises above 1500 °C, FeS and C are added, and then Ti and Al are quickly added until the temperature reaches 1700 °C. Stop heating, stir evenly, and immediately pour it into the sand mold placed on the crystallizer panel. There is a cooling water column at the bottom of the crystallizer panel (pressure is 1.0 Kg, water temperature is 28 °C, water column height is 30 mm (distance from the nozzle to the crystallizer panel)). After 35 min, take down the sand mold, let it stand and cool to room temperature, then unpack it to obtain the blank. Remove the fine crystal part at the bottom and the non-columnar crystal part at the top of the blank to obtain the rough columnar crystal blank.
[0045] 3) Machining: Wire cut the rough columnar crystal blank into the corresponding product shape (D10*45 mm).
[0046] 4) Heat treatment and tempering: Place the blank in a high-temperature furnace at 1280 °C for solution heat treatment for 30 min. Subsequently, take out the rough columnar crystal blank, cool it to 820 °C, then transfer it to a magnetic field, cover it with heat insulation cotton, and place it in the magnetic field for 30 min. After taking it out, directly carry out tempering treatment, specifically, keep it at 610 °C for 4 h, then at 580 °C for 5 h, then at 550 °C for 6 h, and finally air-cool to room temperature to obtain the semi-finished blank.
[0047] 5) Finish machining and inspection: Carry out fine grinding on the semi-finished blank, remove defects such as scale on the surface, clean it, and obtain the product after passing the inspection.
[0048] Example 2
[0049] Take a 20-mm-thick crystallizer panel (45# steel plate), polish the surface smooth and flat, wipe it clean with alcohol, and spray a 2-mm-thick BN coating on the panel surface using the nitrogen plasma spraying process: First, use coating material with D50 = 45 μm and the coating thickness is 0.4 mm; then use coating material with D = 35 μm for spraying, and at this time the coating thickness is 1.0 mm; finally, use coating material with D50 = 30 μm to obtain the crystallizer panel with a uniform coating attached to the surface.
[0050] The subsequent steps are the same as those in Example 1.
[0051] Example 3
[0052] Take a mold shell panel with a thickness of 20 mm (45# steel plate), polish the surface smooth and flat, wipe it clean with alcohol, and spray a BN coating with a thickness of 4 mm on the panel surface using the nitrogen plasma spraying process: First, use a coating material with D50 = 45 μm, and the coating thickness is 0.8 mm; then use a coating material with D50 = 35 μm for spraying, and at this time the coating thickness is 2.0 mm; finally, use a coating material with D50 = 30 μm to obtain a mold shell panel with a uniform coating attached to the surface.
[0053] The subsequent steps are the same as those in Example 1.
[0054] Example 4
[0055] Take a mold shell panel with a thickness of 20 mm (45# steel plate), polish the surface smooth and flat, wipe it clean with alcohol, and spray a Si3N4 coating with a thickness of 2 mm on the panel surface using the thermal spraying process: First, use a coating material with D50 = 45 μm, and the coating thickness is 0.4 mm; then use a coating material with D50 = 35 μm for spraying, and at this time the coating thickness is 1.0 mm; finally, use a coating material with D50 = 30 μm to obtain a mold shell panel with a uniform coating attached to the surface. [[ID=~]]
[0056] The subsequent steps are the same as those in Example 1.
[0057] Example 5
[0058] Take a mold shell panel with a thickness of 20 mm (45# steel plate), polish the surface smooth and flat, wipe it clean with alcohol, and spray an AlN coating with a thickness of 2 mm on the panel surface using the thermal spraying process: First, use a coating material with D50 = 45 μm, and the coating thickness is 0.4 mm; then use a coating material with D50 = 35 μm for spraying, and at this time the coating thickness is 1.0 mm; finally, use a coating material with D50 = 30 μm to obtain a mold shell panel with a uniform coating attached to the surface.
[0059] The subsequent steps are the same as those in Example 1.
[0060] Example 6
[0061] Take a mold shell panel with a thickness of 20 mm (45# steel plate), polish the surface smooth and flat, wipe it clean with alcohol, and spray a composite coating with a thickness of 2 mm (mass ratio of Si3N4, AlN, and BN is 1:1:1) on the panel surface using the thermal spraying process: First, use a coating material with D50 = 45 μm, and the coating thickness is 0.4 mm; then use a coating material with D50 = 35 μm for spraying, and at this time the coating thickness is 1.0 mm; finally, use a coating material with D50 = 30 μm to obtain a mold shell panel with a uniform coating attached to the surface.
[0062] The subsequent steps are the same as those in Example 1.
[0063] Comparative Example 1
[0064] Take a mold shell panel (45# steel plate) with a thickness of 20 mm, polish the surface to be smooth and flat, and wipe it clean with alcohol.
[0065] The subsequent steps are the same as those in Example 1.
[0066] Comparative Example 2
[0067] Take a mold shell panel (45# steel plate) with a thickness of 20 mm, polish the surface to be smooth and flat, and wipe it clean with alcohol; then take kaolin with D50 = 40 μm, mix it evenly with alcohol, and coat it evenly on the mold shell panel with a brush, with a thickness of about 1 mm.
[0068] The subsequent steps are the same as those in Example 1.
[0069] Comparative Example 3
[0070] Take a mold shell panel (45# steel plate) with a thickness of 20 mm, polish the surface to be smooth and flat, and wipe it clean with alcohol; then take BN with D50 = 40 μm, mix it evenly with alcohol, and coat it evenly on the mold shell panel with a brush, with a thickness of about 1 mm.
[0071] The subsequent steps are the same as those in Example 1.
[0072] Comparative Example 4
[0073] 1) Take a mold shell panel (45# steel plate) with a thickness of 20 mm, polish the surface to be smooth and flat, and wipe it clean with alcohol. Spray a 1 mm BN coating on the panel surface by using a nitrogen plasma spraying process: directly select a BN coating material with D50 = 40 μm and obtain a mold shell panel with a uniform coating attached to its surface through one-step spraying.
[0074] 2) The other steps are the same as those in Example 1.
[0075] Comparative Example 5
[0076] 1) Take a mold shell panel (45# steel plate) with a thickness of 20 mm, polish the surface to be smooth and flat, and wipe it clean with alcohol. Spray a 1 mm BN coating on the panel surface by using a nitrogen plasma spraying process: first use a coating material with D50 = 45 μm, and the coating thickness is 0.2 mm; then use a coating material with D50 = 35 μm for spraying, and at this time the coating thickness is 0.5 mm; finally use a coating material with D50 = 30 μm to obtain a mold shell panel with a uniform coating attached to its surface.
[0077] 2) Do not perform any heat treatment on the mold shell panel and use it directly. The other steps are the same as those in Example 1;
[0078] Performance Test
[0079]
[0080] Note: The size of the blank obtained after casting is D50*87mm, 21 pieces per mold.
[0081] It can be seen from the data in the above table that:
[0082] By comparing the fine grain height and the height of the coarse columnar crystal between Example 1 and Comparative Example 1, it can be known that by spraying a dense coating with high thermal conductivity and high temperature resistance on the surface of the mold panel, the height of the coarse columnar crystal in the blank after casting can be effectively increased (the total height of the blank is 87mm, which is composed of a fine grain section, a coarse columnar crystal section and a non-crystalline section in sequence; the smaller the heights of the fine grain section and the non-crystalline section, the higher the quality of the blank), thereby significantly increasing the effective utilization rate of the material (the fine grains at the bottom and the non-columnar crystals at the top of the blank cannot be used to prepare high-performance Alnico); at the same time, the slag eye ratio of the product is also higher. In addition, the setting of the coating can also effectively extend the service life of the mold panel, and increase the production continuity and stability.
[0083] By comparing Example 1 and Comparative Example 2, it can be known that Comparative Example 2 uses kaolin as the coating material. Compared with BN in Example 1, although kaolin can also withstand high temperatures, its thermal conductivity is poor, so it will affect the cooling crystallization rate, and finally the height of the coarse columnar crystal is not as good as that of Example 1, and the slag eye ratio of the product is relatively high. In terms of the service life of the mold panel, Comparative Example 2 is also significantly inferior to Example 1.
[0084] By comparing Example 1 and Comparative Example 3, it can be known that Comparative Example 3 uses the traditional brushing process to form a BN coating. Compared with the plasma spraying process of Example 1, the density of the obtained coating is poor, resulting in a significant increase in the slag eyes of the product, and the service life of the mold panel is significantly inferior to that of Example 1.
[0085] By comparing Example 1 and Comparative Example 4, it can be known that Comparative Example 4 uses a one-step spraying process for the BN coating. Compared with the three-step spraying process of Example 1, the density and thermal conductivity of the obtained coating are poor, resulting in a decrease in the height of the coarse columnar crystal of the product, an increase in slag eyes, and the service life of the mold panel is significantly inferior to that of Example 1.
[0086] By comparing Example 1 and Comparative Example 5, it can be known that in Comparative Example 5, the mold panel is not pre-heat treated, resulting in a significant reduction in the height of the coarse columnar crystal.
[0087] Through the comparison of Examples 1-3, it can be found that when the coating material is the same (BN), with the increase of the coating thickness, the fine grains at the bottom significantly decrease, indicating that the coating can effectively regulate the heat transfer rate, preventing the molten steel just poured into the sand mold from experiencing "undercooling" and generating fine grains or amorphous materials. However, the thicker the coating is not necessarily better. An overly thick coating will affect the heat transfer of the mold panel, resulting in insufficient upward growth power of columnar crystals and a shorter height of columnar crystals (there is a 5-mm amorphous part at the top of the blank obtained in Example 3).
[0088] In summary, the method provided by the present invention for using a plasma spraying coating with high temperature resistance and high thermal conductivity to improve the temperature gradient of the orientation plate and regulate the directional cooling rate not only effectively improves the thickness of the columnar crystals of the oriented alnico magnetic material, enhances the utilization rate and performance of the blank, but also greatly extends the service life of the mold panel and reduces the risks of biting and penetration during continuous production. The blank products processed by the present invention have uniform performance and good appearance, which is of great significance for improving the qualification rate of alnico materials and reducing production hazards.
[0089] Unless otherwise specified, the raw materials and equipment used in the present invention are all common raw materials and equipment in the art; unless otherwise specified, the methods used in the present invention are all conventional methods in the art.
[0090] The above are only the preferred embodiments of the present invention and do not impose any limitations on the present invention. Any simple modifications, changes, and equivalent transformations made to the above embodiments based on the technical essence of the present invention still fall within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a high-quality columnar crystal AlNiCo magnetic material, characterized in that Including: 1) Plasma spray the coating material on the surface of the mold panel: First, use the coating material with a particle size D50 = 40 - 50 μm, and the thickness does not exceed 20% of the total coating thickness; then use the coating material with a particle size D50 = 35 - 40 μm, and the thickness does not exceed 50% of the total coating thickness; finally, use the coating material with a particle size D50 = 30 - 35 μm to form a uniform coating; the coating material is one or more of AlN and BN. 2) Melt and stir the raw materials of alnico, and pour them into the sand mold placed on the mold panel. There is a cooling water column at the bottom of the mold panel. After crystallization, remove the sand mold, let it stand and cool, and then remove the sand mold to obtain a blank. Remove the fine crystal part at the bottom and the non-columnar crystal part at the top of the blank to obtain a rough columnar crystal blank. 3) Process the rough columnar crystal blank into the finished shape. 4) Perform solution heat treatment on the blank with the finished shape, cool it, carry out heat preservation and magnetization, and tempering treatment to obtain a semi-finished blank. 5) Perform finish machining on the semi-finished blank to obtain the finished product.
2. The preparation method according to claim 1, characterized in that: In step 1), the thickness of the mold panel is 15 - 25 mm, and the thickness of the coating is 1 - 4 mm.
3. The preparation method according to claim 1, characterized in that: In step 1), the material of the mold panel is low-carbon steel; Before plasma spraying, grind the surface of the mold panel until it is smooth and flat and clean it. The plasma gas for the plasma spraying is nitrogen.
4. The preparation method according to claim 1, characterized in that: In step 2), the alnico includes the following raw materials in mass percentages: Al 7 - 8%, Co 30 - 35%, Cu 2 - 3%, Ni 12 - 14%, Ti 0.6 - 0.8%, FeS 0.05 - 0.15%, C 0.05 - 0.08%, and the rest is Fe.
5. The preparation method according to claim 4, characterized in that: In step 2), the melting sequence is: First, melt Co, Ni, Cu and Fe. When the molten steel temperature rises above 1500 °C, add FeS and C, then quickly add Ti and Al until the temperature reaches 1650 - 1750 °C, stop heating, stir evenly, and immediately pour.
6. The preparation method according to claim 1, characterized in that: In step (2), the crystallizer panel is heat-treated before use and then cooled to room temperature; the heat treatment temperature is 950 ± 20 °C, the vacuum degree is lower than 5*10 -2 Pa, and the time is 2 - 4 h.
7. The preparation method according to claim 3, characterized in that: In step 2), the melting temperature is 1650 - 1750 °C; the pressure of the cooling water column is 0.8 - 1.2 Kg, the water temperature is 25 - 30 °C, and the water column height is 25 - 35 mm; the crystallization time is 30 - 40 min, and after standing and cooling to room temperature, remove the sand mold.
8. The preparation method according to claim 1, characterized in that: In step 4), the solution heat treatment temperature is 1260 - 1300 °C, and the time is 20 - 40 min; cool it to 800 - 900 °C; the magnetization time is 20 - 30 min; the tempering treatment includes: first, keep it at 610 - 625 °C for 3 - 4 h, then keep it at 580 - 595 °C for 4 - 6 h, then keep it at 550 - 565 °C for 4 - 6 h, and finally air-cool to room temperature.
9. The preparation method according to claim 1, characterized in that: In step 5), the finish machining is to perform fine grinding on the semi-finished blank, remove the surface defects, clean it, and obtain the finished product.
Citation Information
Patent Citations
Quasicrystal coating, preparation method of quasicrystal coating, pot and cooking utensil
CN110754953A
Biomass boiler membrane type water cooling wall sprayed with high-temperature wear-resistant anticorrosive coating
CN212430931U